Faktor yang Memengaruhi Kualitas Hidup Pasien Paska Bedah Pintas Arteri Koroner - Prasetyaningrum, Widyadari; Akbar, M. Rizki; Prawesti, Ayu (Politeknik Kesehatan Tanjung Karang, 2021)
Coronary Artery Bypass Grafting (CABG) is aimed to improve the quality of life among post-CABG patients, there exist a large number of patients having a low level of quality of life. The study aimed to analyze factors that influenced the quality of life among post-CABG patients. The descriptive study was conducted using cross-sectional analysis with a consecutive sampling of 80 post CABG patients in Hasan Sadikin Hospital from 20 May-30 June 2019. Data were analyzed using multivariate linear regression. The independent variables in this study included age, gender, education level, pain, mental health, social support, spiritual well-being, and cardiac rehabilitation. The data were collected using three questionnaires which included Short-Form 36 (SF-36) to measure patient-reported pain, mental health, and the quality of life; Multidimensional Scale of Perceived Social Support (MSPSS) to provide information about the role of social support; and Spirituality Index of Well Being (SIWB) designed to measure the spiritual well-being of the patients. The results showed four factors had significantly influenced the quality of life among patients after CABG. The factors included age (p-value<0,001; r=0,521), pain level (p-value<0,001; r=0,666), mental health (p-value<0,001; r=0,426), and social support (p-value<0,001; r=0,345). Pain factor had the most significant effect on the patients (r=0,497). Pain could cause a stress response that influenced the recovery stage which eventually impacted the quality of life. This study implies that the management of post-CABG patients could be performed by applying pain and stress management in discharge planning.